Home-Coming: The Repatriation of Historical Recordings - Ling Jia Sui [凌嘉穗] (Asian-European Music Research Journal, 2021)
This article deals with the provocative questions of repatriating recordings stored in large and small archival institutions, mainly audio or video recordings, to source communities. While this topic is often, disputed within the framework of sound and audio-visual archivists, it is rather rarely, investigated with academic vigor based personal experience in the field of music research. This paper attempts to start closing the knowledge gap and exchange ideas between those with practical experience and those with musicological background but not necessarily intense experiences. The article provides an in-depth understanding of the term ‘home-coming’ and how this term relates to future activities and directions to be considered by museums and archival institutions. These insights might be of great benefit in sustaining and developing today’s archival institutions in Asia and Europe.